Green Spirituality: The Effect of Spirituality Attitude for Students’ Environment Care Character - Ramli, Supian; Rahman, K. A.; Muspawi, Mohammad; Sobri, Muhammad; Chen, Diki (Jurnal Pendidikan Indonesia, 2022)
Green spirituality is very important to do because it can foster good character development for each individual. The concept of caring for the environment and spiritual attitudes that are very closely related also have a significant impact on the character of students. This study aims to examine the spiritual attitude and character of students' environmental care and their effects. This type of research is a mixed method. The sample used is 35 high school students with the sampling technique used is simple random sampling. The instrument used is a quantitative instrument in the form of a questionnaire of students' spiritual attitudes and environmental care characters, while the qualitative instrument is an interview sheet for students' spiritual attitudes. The analysis technique used is descriptive statistical test and linear regression test. The results obtained in this study are that the sample has a fairly good category for each variable, while for the linear regression test, it shows that there is 50.3% of the influence of spiritual attitudes on the character of students' environmental care. These results indicate that there is a significant influence between spiritual attitudes on the students' environmental care character.